STRATEGI INOVASI PRODUK DAN JASA BERBASIS AKAD WADIAH DAN MUDHARABAH DI ERA DIGITALISASI PERBANKAN SYARIAH - Hasanah Hasanah; Jumardi Jumardi; Bustan Ramli; Sitti Nikmah Marzuki (Universitas Dharmawangsa, 2026)
This study examines how Islamic banks can innovate products and services based on the contracts of wadiah and mudharabah amid rapid digitalization. The research addresses the practical issue of aligning technological advances with Sharia principles while sustaining competitiveness and customer trust. The study aims to (i) map current practices and strategic directions of wadiah mudharabah innovation across digital channels (mobile/internet banking, QRIS, digital wallet), (ii) identify key success factors (contract and profit-sharing transparency, e-service quality, security and Sharia compliance, customer digital literacy, and staff capabilities), and (iii) propose an operational framework linking contract-based innovation to customer outcomes and bank performance. Methodologically, this is a library research drawing on indexed journals, academic books, and prior reports. The synthesis indicates that clear, simple, and secure digital presentation of Sharia values increases customer satisfaction, trust, and loyalty; for banks, it strengthens liquidity (via wadiah funds), reduces cost of funds in mudharabah portfolios, lowers operating costs, and expands the customer base. The proposed three tier framework contract, process & technology, and outcomes—supported by blockchain, big data analytics, and AI, guides practical implementation and measurement.